PENETAPAN NERACA AIR TANAH MELALUI PEMANFAATAN INFORMASI KLIMATIK DAN KARAKTERISTIK FISIK TANAH - Laode Sabaruddin; Hasbullah Syaf; La Ode Afa; L.M. Hardjoni Kilowasid (Universitas Haluoleo, 2015)
Utilization of climatic information and physical characteristics of the soil to determine the soil water balance in agriculture is a very important factor because it relates to the planning model of activity to be undertaken. This is important because the output is known a periods of surplus and deficit water of the regions. Periods of surplus and deficit is implications for the length of growth period available to facilitate the planning of agricultural models that will be developed. The planning agricultural model is still oriented to the needs of farmers and the willingness of the government, not based on the climatic information and physical characteristics of the soil. Keywords : climatic information, soil characteristics, water balance.